The influence of green marketing, product knowledge, and influencers on purchase intention - Rina Sugiarti; Nenik Diah Hartanti; Ekaning Setyarini; Sri Kurniasih Agustin (International Journal on Social Science, Economics and Art, 2023)
This study aims to analyze the influence of green marketing, product knowledge and influencers on purchase intention of Avoskin cosmetic products. Respondents in this study are educated generation Z who live in Jabodetabek who have the intention to purchase Avoskin cosmetic products. The sampling method uses non probability sampling with accidental sampling technique. The data source is primary data obtained by distributing questionnaires to respondents which are measured through several indicators of each related variable. The test stages carried out are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, F test and t test. The results showed that green marketing and influencers have an effect on purchase intention, while product knowledge has no effect on purchase intention.